Factors Influencing Public Concern about Environmental Protection: An Analysis from China - Xinlei Yang; Xiucheng Dong; Qingzhe Jiang; Guixian Liu (Discrete Dynamics in Nature and Society)
This paper uses the Baidu Index to construct indicators for measuring the public's environmental concerns in 288 prefecture-level cities in China from 2011 to 2016 and validates the public's attention to the effectiveness of environmental indicators by using provincial panel data from public environmental reports. Through the analysis of urban heterogeneity, the impact on the development of informatisation on the public's concern for the environment is considered. Also studied is the cross-cutting effect of the level of informatisation and education, the government's environmental regulation power, economic development level, and environmental pollution level on the public's concern for the environment. The influence coefficients were 0.018, 0.147, 0.689, 0.620, 0.106, and 0.089, respectively. Through subsample heterogeneity analysis, we found that the level of informatisation will also indirectly promote public attention to the environment by strengthening the influence of the government's environmental regulation power on the public's attention to the environment.